2015
DOI: 10.1186/s12889-015-1995-8
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of delivery modes for lifestyle advice in a large scale randomised controlled obesity prevention trial

Abstract: BackgroundPreventing obesity is an international health priority and women living in rural communities are at an increased risk of weight gain. Lifestyle programs are needed as part of a comprehensive approach to prevent obesity. Evaluation provides a unique opportunity to investigate and inform improvements in lifestyle program implementation strategies. The Healthy Lifestyle Program for rural women (HeLP-her Rural) is a large scale, cluster randomized control trial, targeting the prevention of weight gain. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…2). As previously reported, n  = 649 women were recruited, representing ~10% of the eligible target population [47, 50]. Based on predefined and limited exclusion criteria, less than 12% of volunteers ( n  = 95) were excluded post screening (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2). As previously reported, n  = 649 women were recruited, representing ~10% of the eligible target population [47, 50]. Based on predefined and limited exclusion criteria, less than 12% of volunteers ( n  = 95) were excluded post screening (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative participant interviews revealed that group education sessions were most valued, followed by text messages and phone coaching. Overall, delivery of lifestyle advice through multiple delivery modes (group sessions, phone coaching, text messages, and a program manual) was recommended by participants to optimize program acceptability and accommodate diverse learning styles [47]. A full economic analysis is underway based on a pending 2-year data analysis and will be reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations